2021
DOI: 10.3390/ijerph18042086
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Artificial-Intelligence-Driven Differential-Diagnosis List on the Diagnostic Accuracy of Physicians: An Open-Label Randomized Controlled Study

Abstract: Background: The efficacy of artificial intelligence (AI)-driven automated medical-history-taking systems with AI-driven differential-diagnosis lists on physicians’ diagnostic accuracy was shown. However, considering the negative effects of AI-driven differential-diagnosis lists such as omission (physicians reject a correct diagnosis suggested by AI) and commission (physicians accept an incorrect diagnosis suggested by AI) errors, the efficacy of AI-driven automated medical-history-taking systems without AI-dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…As a result, that study showed that the AI-driven DDSS with AI-driven AMHT system also led to omission and commission errors at similar rates as did the type of DDSS that generated differential diagnoses after physicians enter the key symptoms and findings after a clinical encounter [ 10 ]. The following study, which we reported recently, also confirmed the findings [ 17 ]. However, these studies did not assess the mechanism of omission and commission errors when using this new type of DDSS.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…As a result, that study showed that the AI-driven DDSS with AI-driven AMHT system also led to omission and commission errors at similar rates as did the type of DDSS that generated differential diagnoses after physicians enter the key symptoms and findings after a clinical encounter [ 10 ]. The following study, which we reported recently, also confirmed the findings [ 17 ]. However, these studies did not assess the mechanism of omission and commission errors when using this new type of DDSS.…”
Section: Introductionsupporting
confidence: 89%
“…According to a previous study, task performance can worsen by using an automated rather than a manual procedure when the reliability of automation is <70% [ 20 ]. As the reliability of AI in this study was set at 50% (the correct diagnosis was listed in 8 of 16 cases), approximately 15% of the effect of the DDSS on the physicians’ differential diagnosis may be associated with the commission errors observed in our main analysis [ 17 ]. The prevalence of diagnoses identical with the differential diagnosis of AI was also approximately 15% higher in the intervention group than in the control group, even in the subset of AI incorrect cases, which led to commission errors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations